Geomythology as a Geotourism Attraction, Case Study: The Sangkuriang Legend in The Bandung Highland and Its’ Surrounding Areas Based on Geological to Hermeneutics Interpretation - Oman Abdurahman; Denny Sukamto Kadarisman (Badan Pelaksana Rinjani-geopark Rinjani Lombok, 2022)
The Bandung Highlands and its surrounding areas (BHLs) are rich in important geodiversity and geoheritage sites because of its values. They are of knowledge value, educational value, environmental value, cultural value, economic value, and others. An important one is the value of tradition in the form of legend, in this case the Sangkuriang in the Sunda community - the majority of the population is in BHLs - even in the archipelago. All of them have made the BHLs area an important geotourism destination in West Java. Meanwhile, the development of a new sub-discipline called